The Impact of Interbank Offered Rate on the Exchange Rate of the Chinese Yuan Renminbi Against the Sterling Pound: Evidence from Libor and Shibor - Shi, Junchi; Wu, Maoguo (European Scientific Journal, ESJ, 2018)
United Kingdom, as the world’s fifth largest economy, maintains good cooperation relation with China in the area of economy and trade. As the world’s fourth largest foreign exchange trading currency, the exchange rate fluctuation of the sterling pound has an important economic impact on the world’s foreign exchange market and it also has a significant impact on the trade with China. There are many factors that influence the exchange rate. By using time series approach, this paper analyzes the impact of two main variables, Libor and Shibor, and five common economy variables, inflation rate, interest rate, balance of trade, GDP and money supply, on the change of the sterling pound exchange rate. The results of the empirical analysis show that five common factors have significant relation with exchange rate. For the two main variables, Libor has a strong correlation with the sterling pound exchange rate, but Shibor has no such relation. Meanwhile, this paper focuses on analyzing the possibility of arbitrage according to the empirical results. It was found that the model for the impact on exchange rate in this paper cannot predict future exchange rate. As a result, short-term arbitrage prediction cannot be made.